The Advanced Lung Cancer Inflammation Index and Mortality in Patients with Cardiovascular-Kidney Metabolic Syndrome: Insights from NHANES - Xiaohan Ma; Xin Tang; Sheng Chen; Tong Wu; Peiling Zuo; Fasheng Wu; Encun Hou; Xiaofei Zhang (BMC Cardiovascular Disorders)
Abstract Background The advanced lung cancer inflammation index (ALI) is a marker of inflammation, yet its prognostic value in cardiovascular-kidney-metabolic (CKM) syndrome has not been explored. This study examines the relationship between ALI and mortality risk in patients with CKM. Methods We analyzed data from 14,301 CKM patients in the National Health and Nutrition Examination Survey (1999–2018). We assessed ALI tertiles (Tertile 1–Tertile 3) using Cox regression, restricted cubic splines, Kaplan-Meier survival curves, and receiver operating characteristic curves. We also performed sensitivity analyses to confirm the robustness of our results. Results In a cohort of 14, 301 patients with CKM syndrome, 2,418 deaths from all causes, 765 cardio-cerebrovascular deaths, and 590 cancer-related deaths were recorded. After adjusting for potential confounders, the weighted multivariate Cox model showed that higher ALI was significantly associated with a reduced risk of all-cause and cardio-cerebrovascular mortality (all P < 0.001). However, a correlation between ALI scores and reduced cancer mortality was only observed in Tertile 2 for cancer mortality (P= 0.01). Smooth curve fitting revealed nonlinear correlations between ALI and mortality across CKM stages 0–4, 0–3, and 4 (log-likelihood ratio test P < 0.001). Stratified analyses identified significant interactions between age (P for interaction = 0.03) and smoking status (P for interaction < 0.001) with all-cause mortality, and between chronic kidney disease prognosis and cancer mortality (P for interaction = 0.03) in CKM syndrome patients. Receiver operating characteristic curves confirmed that ALI is a strong predictor of both short- and long-term all-cause, cardio-cerebrovascular, and cancer mortality. Conclusion Our study shows that ALI is negatively correlated with all-cause, cardio-cerebrovascular, and cancer mortality within a certain range in patients with CKM syndrome. ALI is an effective prognostic predictor of mortality risk in individuals with CKM syndrome.